The Influence of Artificial Intelligence in Digital Marketing on Generation Z Consumer Decision Making - Azka Zharfan Ash Shiddieqy; Tri Widarmanti (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the impact of Artificial Intelligence (AI) usage in digital marketing on Generation Z consumers' decision-making. In the rapidly growing digital era, the implementation of AI in marketing strategies has become crucial in attracting attention and influencing consumer behavior. This research employs a modified Technology Acceptance Model (TAM) to analyze the factors affecting Generation Z's purchase intention, with independent variables including ad personalization, Chatbots, AI-based recommendations, and AI-supported Augmented Reality (AR). Additionally, the study examines mediating variables such as trust in AI technology and moderating variables such as loyalty toward platforms using AI. The research employs a quantitative approach using a questionnaire as the data collection instrument. The respondents are 384 Generation Z consumers who actively shop online and interact with AI technology. Data analysis techniques include PLS-SEM (Partial Least Squares Structural Equation Modeling) to test relationships between variables and IPA (Importance-Performance Analysis) to assess the performance and importance of variables related to purchase intention. The analysis results indicate that the use of AI technology in digital marketing has a significant positive impact on Generation Z consumers' decision-making, with trust in AI technology serving as a significant mediating variables. Moreover, loyalty to brands using AI plays a moderating role in this influence.